2019
DOI: 10.1097/shk.0000000000001202
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Safety of Corticosteroids Therapy in Adult Critical Ill Patients With Septic Shock: A Meta-Analysis of Randomized Controlled Trials

Abstract: Based on the results of this meta-analysis, corticosteroids therapy was associated with a significantly shorter length of stay in ICU among adult cirtical ill patients with septic shock. The mortality was similar between the corticosteroids therapy and placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
2
0
3
Order By: Relevance
“…Based on extensive search in PubMed and Embase, we found 8 systematic reviews and meta-analyses 18-20 50-54 on the use of corticosteroids in patients with sepsis had been published since 2018. Although all of these reviews included the two largest RCTs, the ADRENAL trial 3 and the APROCCHSS trial, 2 and included a substantial number of other RCTs, they reported contradictory results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on extensive search in PubMed and Embase, we found 8 systematic reviews and meta-analyses 18-20 50-54 on the use of corticosteroids in patients with sepsis had been published since 2018. Although all of these reviews included the two largest RCTs, the ADRENAL trial 3 and the APROCCHSS trial, 2 and included a substantial number of other RCTs, they reported contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…Although all of these reviews included the two largest RCTs, the ADRENAL trial 3 and the APROCCHSS trial, 2 and included a substantial number of other RCTs, they reported contradictory results. In particular, 4 reviews 18 19 50 51 reported that corticosteroids significantly reduced the risk of 28-day mortality, but other four studies 20 52-54 found that intravenous corticosteroids did not lower the risk of either short-term or 28-day mortality. In addition to possible factors such as various outcome definitions or different modeling approaches, we argued that the mixed findings can only be clarified if we first properly standardized the inconsistent definitions for sepsis across previous trials.…”
Section: Discussionmentioning
confidence: 99%
“…Conforme o estudo realizado, os resultados encontrados foram divididos em: artigos que mostraram efeitos e resultados positivos da corticoterapia adjuvante no choque séptico (Annane, 2019;Antcliffe & Gordon, 2019;El-Nawawy, Khater, Omar, & Wali, 2017;Fang et al, 2018;Garza et al, 2018;Gibbison et al, 2017;Law, Sahetya, Walkey, & Delaney, 2018;Lee & Yeh, 2018;Lian et al, 2019;Liu & Menon, 2018;Menon & Mcnally, 2018;Meyer et al, 2019;Pourmand, Whiteside, Yamane, Rashed, & Mazer-Amirshahi, 2019;Russell, 2018. Wen et al, 2019Wong et al, 2016;Zhou, Ye, Li, & Tang, 2018), e resultados negativos do uso complementar dos corticosteroides no choque séptico (Cvijanovich et al, 2017;Lemieux, Levine, & Gritsenko, 2019;Long & Koyfman, 2017;Moskowitz et al, 2020;Salluh & Póvoa, 2017;Yang & Sun, 2020;Zimmerman, 2018).…”
Section: Gráfico 1 Anos De Publicação Dos Artigosunclassified
“…Além disso, levando em consideração os 90 dias, a mortalidade na UTI e a intra-hospitalar, o tempo de permanência hospitalar, a reversão do choque e a superinfecção não tiveram diferença significativa entre a terapia com corticosteroides e a terapia com placebo. Esses resultados foram obtidos ao considerar dosagens tanto baixas quanto altas de corticoides (Wen et al, 2019).…”
Section: Gráfico 1 Anos De Publicação Dos Artigosunclassified
See 1 more Smart Citation